Gravity anomaly and basis symmetric matrix Interpretation for residuals (2018)
Gravity method has tremendously pervaded the field of geophysical exploration and thus extensively discussed and vividly illustrated in this work. The basis for symmetric matrix data gravity interpretation was earlier proposed, then extended to residuals and interpretation. A symmetric matrix representation is discussed further to residuals, spectral, interpretation, and optimistically forms a veritable tool for gravity data interpretation. The fundamental law of gravitational attraction is essential in delineating gravity data interpretation and the gravity effect or anomaly representation is evidently expressed by a finite difference matrix in the discussion. A computational extension can be done based on the symmetric matrix representation with available gravity data and a vivid illustration for anomaly and residual computation has been made